O'Brien, Aloysius 5. Interview about animals - Shawyer; Jo (1992)
Aloysius mainly talked about the cows, pigs,poultry and grazing. "0:00-05:00 cows paths; walking cows; 05:00-10:00 cow management; pig; pig feed; cow feed; 10:00-15:00 pig feed; cow feed; breed of cows 15:00-20:00 milking; sickness of cows; vet; grass for cows; 20:00 - 25:00 supplement food for cows; dealer; milking 25:00 – 30:00 pig; chickens 30:00-35:00 poultry farm; killing chicken; 35:00-40:00 cats; graze; 40:00 – 45:00 fields for grazing; the changes on the fields 45:00- 50:00 land sold to Botanical Gardens; 50:00- 54: 36 relatives; different skills of the three brothers; delivering milk "